Multihoming Support towards Always Best Connected Service in Heterogeneous Wireless Networks - Wang, Qi; Fyfe, Colin; Crowe, Malcolm (Recent Patents on Computer Science, 2010)
The last decade has witnessed rapid development of diverse emerging wireless systems such as the thirdgeneration (3G) and beyond wide-area cellular networks, municipal area networks and local area hotspots. It is widely envisioned that these coexisting heterogeneous networks could complement each other in capacity and coverage and would converge into a common platform over the Internet Protocol (IP). In line with the converged networks, user devices equipped with multiple network interfaces are being shipped. Consequently, a nomadic customer with such a multihomed device would expect to experience improved quality of service (QoS) by optimally utilising available access networks surrounding him/her on the move, and thus to be always best connected (ABC). This paper reviews recent patents, together with related standards and typical academic proposals, on supporting multihoming towards enabling the ABC service. Multihoming protocols being standardised are investigated first, following an introduction to heterogeneous and converged networks and essential multihoming and ABC concepts. Subsequently, a survey is performed on the two core components in multihoming ABC paradigm: intelligent network selection and multihoming handover with both concurrent communication via multiple interfaces and inter-system handover schemes covered. Finally, views on current and future development are provided.
Keywords: always best connected